A new species of Pleurothallis (Pleurothallidinae:Orchidaceae) from subgenus Ancipitia discovered through citizen science in the paramo of the Central Andes of Colombia - Sánchez-Gómez, David; Gallego-Franco, Yudy; Wilson, Mark (Phytotaxa, 2025)
A new species of Pleurothallis (subgenus Ancipitia) is described from the paramos of the Central Andes of Colombia, discovered through citizen science. Pleurothallis maitamae belongs to the P. crocodiliceps complex and is apparently endemic to the paramo fragment of Cerro de Las Palomas, in the municipality of Sonsón, Antioquia at elevations between 2600–3000 meters. This species is distinguished by its robust, medium-sized habit and unique floral morphology, particularly its chestnut-colored, 3-lobed labellum with horn-like lateral lobes and pale yellow to cream-colored flowers with dark-purple spots. Detailed comparisons with morphologically similar species in the complex, including P. andreae, P. ecomingae, P. onagriceps, and P. wielii confirm its distinctiveness. It is also compared with the similar species P. dunstervillei, which is not a member of the P. crocodiliceps complex, but which is similar in general floral features. This discovery highlights the importance of integrating citizen science with traditional taxonomic research to uncover biodiversity in understudied ecosystems such as the Andean paramos.